Control of Pythium wilt and root rot of hydroponically grown lettuce by means of chemical treatment of the nutrient solution - Labuschagne, Nico (University of Pretoria, 2013)
Dissertation (MSc (Plant Pathology))--University of Pretoria, 2008.